Structures of CUG repeats in RNA. Potential implications for human genetic diseases. - Pinheiro, P; Scarlett, G; Rodger, A; Rodger, P; Murray, A; Brown, T; Newbury, S; McClellan, J (2002)
Triplet repeats that cause human genetic diseases have been shown to exhibit unusual compact structures in DNA, and in this paper we show that similar structures exist in shorter "normal length" CNG RNA. CUG and control RNAs were made chemically and by in vitro transcription. We find that "normal" short CUG RNAs migrate anomalously fast on non-denaturing gels, compared with control oligos of similar base composition. By contrast, longer tracts approaching clinically relevant lengths appear to form higher order structures. The CD spectrum of shorter tracts is similar to triplex and pseudoknot nucleic acid structures and different from classical hairpin spectra. A model is outlined that enables the base stacking features of poly(r(G-C))(2).poly(r(U)) or poly(d(G-C))(2).poly(d(T)) triplexes to be achieved, even by a single 15-mer.